P71 Remote respiratory sampling and unusual Pseudomonas growths in adults with cystic fibrosis: Is there a link?. (11th November 2022) - Ur Rehman, K; Tausan, M; Ramadan, N; Felton, I; Ukor, E; Madge, S; Jones, A; Simmonds, NJ
Abstract : Introduction and Objectives: In our adult cystic fibrosis (CF) centre, we anecdotally observed an increasing number of unusual Pseudomonas growths from respiratory samples. This coincided with the introduction of remote (postal) respiratory sampling (cough swabs/sputum) mostly driven by Covid19 pandemic. We aimed to quantify this observation by analysing microbiological trends since the introduction of remote sampling, describe treatment interventions and explore possible reasons for changes identified. Methods: Cough swab and sputum data were collected retrospectively over two 6-month time periods: 2019 and 2021 (Mar-Sep). Additional data were collected on demographics and treatment outcomes for unusual Pseudomonas growths. Any Pseudomonas growth other than Pseudomonas aeruginosa was defined as 'unusual'. Culture techniques were unchanged throughout the study period. Processing time = date sample received in lab – date sample requested. Results: 1911 respiratory samples (n=0 remote) were received in the 6-month period in 2019, compared to 966 samples (n=557 [57.7%] remote) in 2021. No statistically significant difference was found in sputum to cough swab ratio in 2019 (85.2%:14.8%) and 2021 (87.4%:12.6%; p =0.12). Among 1604 (83.9%) positive samples in 2019, 20 (1.3%) were unusual Pseudomonas growths v. 46 (5.5%) in 844 (87.4%) positive samples in 2021 ( p <0.001). In 2021, across all samples, unusual Pseudomonas growths occurred after a median (IQR) processing time of 3 (5) days v. 2 (4) for all other positive samples ( p =0.03). Remote samples were processed at a median of 2 (5) days v. 1 (3) day for non-remote (p<0.001). Characteristics of both cohorts with unusual Pseudomonas growths are summarised in table 1 . Conclusion: Despite nearly 50% reduction in respiratory sampling (likely a result of Covid19 and the introduction of the CFTR modulator 'Kaftrio'), our study demonstrated more than a 2-fold increase in growths of unusual Pseudomonas species in 2021. We found an association with longer processing times, which were more common with remote sampling. Mechanisms underlying this, such as contamination, require further investigation. Importantly, our data suggest that growths may be transient and treatment not always indicated. Our results suggest caution should be exercised when interpreting samples with long processing times, but further prospective studies are required.